The EAGLE model for Hungary: A global perspective - Lászlo Békési; Lóránt Kaszab; Szabolcs Szentmihályi (Magyar Nemzeti Bank, 2017)
In this paper we adopt the Hungarian version of the EAGLE (Euro Area GLobal Economy) model. The version of the EAGLE model used in this paper allows for the high import content of export - a typical feature of small open economies such as Hungary. We study the effects of four globally important shocks on Hungary: i) a slowdown of the Chinese economy, ii) more restrictive US monetary policy, iii) a reduction in oil prices, and iv) more protectionist US trade policy. We found these policies to have nonnegligible indirect effects (beyond the relatively small direct ones) on Hungary mostly due to the workings of the shock to the eurozone which is our main trade partner.
Keywords: E12; E13; E52; E58; F11; F41; 330; Multi-country DSGE; price and wage rigidity; EAGLE model; trade matrix; import content of export; local currency pricing; monetary policy shock; consumption preference shock; markup-shock